Fighting the COVID-19 Pandemic - Mohammad Baddour, Manal (IntechOpen, 2021)
During the past two years, the world has been fighting the COVID-19 pandemic, which has had many negative effects on people's quality of life, physical health, and mental health. Nobody is oblivious to the general information related to the virus or the deleterious health effects it has been linked to, yet there is a lot more to it than the general knowledge. In this book, we shed light on the virus itself and its properties, epidemiology, immune response, various clinical scenarios and consequences, and diagnostic and management dilemmas. Finally, we discuss COVID vaccines and the related myths and misinformation that have led to vaccine hesitancy and mistrust.